INFLUENCE OF THE BOARD OF COMMISSIONERS AND FINANCE PERFORMANCE ON SUSTAINABILITY REPORTS - Bambang Sugiharto; Muhammad Abdul Malik; Indah Umiyati (ZILLZELL MEDIA PRIMA, 2024)
This research aims to determine the influence of the board of commissioners, company size and profitability on sustainability reports. The population used in this research is state-owned companies that report annual reports consistently in 2021-2022. The analytical method used in this research is logistic regression with the SPSS version 25 for Windows program. The population in this research is all state-owned companies, totaling 63 companies. The sample was determined based on the purposive sampling method totaling 126 companies. The data used in this research is secondary data. Partially, the results of this research show that the board of commissioners and company size influence the sustainability report. Profitability does not have a significant effect on the sustainability report. Simultaneously, the results of this research show that the board of commissioners, company size and profitability simultaneously influence the sustainability report.